Business management a contemporary approach - Nieuwenhuizen, C. (Cecile); Rossouw, D. (Dirk) (Juta and Company Ltd, 2008)
The world is in a constant state of flux, and this influences the operations of every business and organisation. This book deals with these changes by covering the functions of a business or an organisation and then addressing the contemporary issues that affect them.